The Dynamics of the Slow Flow of a Singular Damped Nonlinear System and It Parametric Study - Maaita, J.O.; Meletlidou, E.; Vakakis, A.F.; Rothos, V. (Journal of Applied Nonlinear Dynamics, 2026)
We study the dynamical behavior of the slow flow of a three degree of freedom dissipative system of linear coupled oscillators with an essentially nonlinear attachment and compare the behavior of the initial system to the Slow Invariant Manifold (SIM). The dynamics of the slow flow can be simple, making regular oscillations in the region of the stable branches of the SIM, having relaxation oscillations or chaotic behavior.The initial system oscillates in the region of the SIM, verifying that the SIM plays an essential role for the dynamics of the initial system.